The TRH test provides valuable information in the diagnosis of central hypothyroidism in patients with known pituitary disease and low T4 levels - Christensen, Sara Ellegaard; Smith, Liv Norma; Rosendal, Christian Alexander H.; Gulisano, Helga Angela; Ettrup, Kåre Schmidt; Vestergaard, Peter; Nielsen, Eigil Husted; Karmisholt, Jesper Scott; Dal, Jakob (Frontiers in Endocrinology, 2023)
Objective: To evaluate the value of the thyrotropin-releasing hormone (TRH) test in the diagnosis of central hypothyroidism (CH) in patients with pituitary disease.Methods: Systematic evaluation of 359 TRH tests in patients with pituitary disease including measurements of thyroxine (T4), TBG-corrected T4 (T4corr), baseline TSH (TSH0) and relative or absolute TSH increase (TSHfold, TSHabsolute).Results: Patients diagnosed with CH (n=39) show comparable TSH0 (p-value 0.824) but lower T4corr (p-value <0.001) and lower TSH increase (p-value <0.001) compared to patients without CH. In 54% (42 of 78 cases) of patients with low T4corr, the CH diagnosis was rejected based on a high TSHfold. In these cases, a spontaneous increase and mean normalization in T4corr (from 62 to 73 nmol/L, p-value <0.001) was observed during the follow-up period (7.6 ± 5.0 years). Three of the 42 patients (7%) were started on replacement therapy due to spontaneous deterioration of thyroid function after 2.8 years. Patients diagnosed with CH reported significantly more symptoms of hypothyroidism (p-value 0.005), although, symptoms were reported in most patients with pituitary disease. The TRH test did not provide clinical relevant information in patients with normal T4 or patients awaiting pituitary surgery (78 %, 281 of 359). There were only mild and reversible adverse effects related to the TRH test except for possibly one case (0.3%) experiencing a pituitary apoplexy.The TRH test could be reserved to patients with pituitary disease, low T4 levels without convincing signs of CH. Approximately 50 % of patients with a slightly decreased T4 were considered to have normal pituitary thyroid function based on the TRH test results. Kommenterede [JD1]: OBS det skal jo lave til en reference Kommenterede [JD2R1]: CR fjern gerne den tomme fod note igen :)